(2x-1)(5x-5)=

Simple and best practice solution for (2x-1)(5x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(5x-5)= equation:


Simplifying
(2x + -1)(5x + -5) = 0

Reorder the terms:
(-1 + 2x)(5x + -5) = 0

Reorder the terms:
(-1 + 2x)(-5 + 5x) = 0

Multiply (-1 + 2x) * (-5 + 5x)
(-1(-5 + 5x) + 2x * (-5 + 5x)) = 0
((-5 * -1 + 5x * -1) + 2x * (-5 + 5x)) = 0
((5 + -5x) + 2x * (-5 + 5x)) = 0
(5 + -5x + (-5 * 2x + 5x * 2x)) = 0
(5 + -5x + (-10x + 10x2)) = 0

Combine like terms: -5x + -10x = -15x
(5 + -15x + 10x2) = 0

Solving
5 + -15x + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '5'.
5(1 + -3x + 2x2) = 0

Factor a trinomial.
5((1 + -2x)(1 + -1x)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {0.5, 1}

See similar equations:

| 4r-4=(r-4)(r-4) | | 0.6x-1.9y+3.2=0 | | 160=3x+y | | -9y+19=4y-7 | | 1-4.9x^2=0 | | (w-4)/4w=1/5 | | 12y-7+1+4y= | | ix=3x | | 7-2y=10-6y+4y | | x(x-3)=16/3 | | -3(5u-2)+5u=4(u+4) | | 3(4y)=24 | | 6(x-3)=9x-24 | | 2(6d+3)=18-48+9d | | X+(x-5)=20 | | 10.2u+0.5=2.5u-0.3(u-7) | | 2x^2+12x+19=x^2+8x+16 | | X^2+10+25=245-2x | | 4x+20=2x+34 | | 2x^3+3x^2+5x+2=0 | | -22=5(u-2)-8u | | F(x)=log(x-4)-3 | | 3x+1x+24=28x | | 10x-(12x+8)=12 | | (x-1)*(x-1)*(x+4)=0 | | 21x^2=-17x+8 | | H=4+63t-63t^2 | | 7/10x=3 | | 17x-32=53 | | 2x^2+5x+24=0 | | T-5.2=3.25 | | 2r^3+3r^2-2r-3=0 |

Equations solver categories